2009
DOI: 10.1016/j.yebeh.2009.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Basal cortisol is positively correlated to threat vigilance in patients with psychogenic nonepileptic seizures

Abstract: a b s t r a c tPrevious studies have provided evidence for a vigilant attentional bias toward threat stimuli and increased basal diurnal cortisol levels in patients with psychogenic nonepileptic seizures (PNES). Because cortisol levels may be predictive of threat vigilance, we reanalyzed previous data on threat vigilance in 19 unmedicated patients with PNES and found a positive correlation between baseline cortisol levels and attentional bias scores for threat stimuli (r = 0.49, P = 0.035). There was no such r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 16 publications
4
35
0
Order By: Relevance
“…In line with this, Bakvis and colleagues (2010) demonstrated patients with psychogenic non-epileptic seizures have higher levels of baseline cortisol, indicative of higher stress state. These patients also showed increased avoidance behaviour, compared to controls, in a task requiring directional movements towards or away from their body in response to angry (but not happy) faces, consistent with a defensive strategy to cope with impending threat (Bakvis et al, 2009a(Bakvis et al, , 2009b(Bakvis et al, , 2011. Additionally, increased activity in the periaqueductal gray (PAG) and SMA was found in FND patients during processing of negative (sad and fearful) faces, indicating modulation of defense-like behaviour to aversive stimuli (Aybek, et al, 2015).…”
Section: Introductionmentioning
confidence: 73%
“…In line with this, Bakvis and colleagues (2010) demonstrated patients with psychogenic non-epileptic seizures have higher levels of baseline cortisol, indicative of higher stress state. These patients also showed increased avoidance behaviour, compared to controls, in a task requiring directional movements towards or away from their body in response to angry (but not happy) faces, consistent with a defensive strategy to cope with impending threat (Bakvis et al, 2009a(Bakvis et al, , 2009b(Bakvis et al, , 2011. Additionally, increased activity in the periaqueductal gray (PAG) and SMA was found in FND patients during processing of negative (sad and fearful) faces, indicating modulation of defense-like behaviour to aversive stimuli (Aybek, et al, 2015).…”
Section: Introductionmentioning
confidence: 73%
“…Evidence of this has been provided by HRV studies as well as by a study comparing cortisol day curves in patients with PNES and healthy controls [28][29][30]. In another study, the elevated resting cortisol levels detected in patients with PNES were found to be positively correlated with increased threat vigilance [31].…”
Section: Physiological Changesmentioning
confidence: 93%
“…Cortisol levels of patients with PNES were also elevated in a study of automatic avoidance [27]. Furthermore, levels of baseline cortisol in patients with PNES were positively correlated with an attentional bias to threatening social stimuli [28].…”
Section: Introductionmentioning
confidence: 89%